KAJIAN PEMANFAATAN WARNA DAN ILUSTRASI SEBAGAI MEDIA PENDUKUNG PENGEMBANGAN POTENSI KAMPUNG TEMATIS DI KOTA MALANG JAWA TIMUR - Wahyu Sukayasa, Komang (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
Unorganized urban areas are a distinct problem arising from urban development that demands appropriate solutions. One way to address this issue is to transform the area into a thematic village by adding a touch of beauty to transform its appearance, emphasizing the potential of art and culture. One of the most frequently chosen and implemented elements as an essential element of a thematic village is the use of color on the houses in the location, which also serves as a marker and pictorial elements in the form of murals, illustrations, and aesthetic elements that function as a space-filling medium in the location. The problem encountered is the importance of understanding the concept of arranging visual elements, especially color and images, as an effort to realize a sustainable concept containing art and culture to maintain and enhance the sustainability of the unique potential of the thematic village. The research method used is a basic approach to visual arts and design. The elements that are emphasized are the analysis of color, shape, composition, space, and movement, combined with an approach to understanding the theory of drawing and illustration. The potential of color and images is very broad and if applied conceptually, it will become a potential solution in the form of a sustainable and long-term preservation and development of the thematic village concept.